Successful Application of the Gamma-Interferon Assay in a Bovine Tuberculosis Eradication Program: The French Bullfighting Herd Experience - Keck, Nicolas; Boschiroli, Maria-Laura; Smyej, Florence; Vogler, Valérie; Moyen, Jean-Louis; Desvaux, Stéphanie (Frontiers in Veterinary Science, 2018)
In the French Camargue region, where bovine tuberculosis had been enzootic for several years in bullfighting cattle herds, the interferon gamma (IFN) test was used since 2003 in parallel with the intradermal test in order to increase overall disease detection sensitivity in infected herds. This study presents the results of a field-evaluation of the test during a 10-years period (2004-2014) of disease control and surveillance program and explores the particular pattern of IFN test results in bullfight herds in comparison to cattle from other regions of France. Although being quite low, the individual sensitivity rate (59.2% [50.6; 67.3]) of IFN test using the tuberculins’ stimulation remains much higher than those of the SICT in this particular epidemiological context. This low sensitivity could be related to the poor IFN production of bullfight infected cattle blood cells which is significantly lower than in animals of conventional breeds. The characteristics of the test were progressively adapted to the epidemiological situation and the desired strategic applications. Data analysis with a ROC curve based on a simple S/P value algorithm allowed determining a new cut-off adapted for a global screening, giving good specificity results and a high accuracy of the test. Having regularly risen to above 5% since 2005, with a peak around 10% in 2010, the annual incidence dropped to under 1% in 2014. The positive predictive value evolved during the years, from 33% in 2009 to 12% during the last screening period, a normal trend in a context of decreasing prevalence. The estimated rate of apparent false positive reactions during screening campaigns was 0.67%, showing that specificity was under control. The proportion of false positive reactions decreased with the age and was higher in males than in females. Although these results indicate that the IFN test is accurate in the field, it also emphasizes great differences between interferon quantity produced by bullfight cattle blood samples compared to those of classical bovine breeds, which underlines the necessity to adapt the algorithms and combinations of the tests according to local epidemiological contexts.